Golf Swing Biomechanics: A Systematic Review and Methodological Recommendations for Kinematics - Maxime Bourgain; Philippe Rouch; Olivier Rouillon; Patricia Thoreux; Christophe Sauret (MDPI AG, 2022)
Numerous studies have been conducted to investigate golf swing performance in both preventing injury and injury occurrence. The objective of this review was to describe state-of-the-art golf swing biomechanics, with a specific emphasis on movement kinematics, and when possible, to suggest recommendations for research methodologies. Keywords related to biomechanics and golf swings were used in scientific databases. Only articles that focused on golf-swing kinematics were considered. In this review, 92 articles were considered and categorized into the following domains: X-factor, crunch factor, swing plane and clubhead trajectory, kinematic sequence, and joint angular kinematics. The main subjects of focus were male golfers. Performance parameters were searched for, but the lack of methodological consensus prevented generalization of the results and led to contradictory results. Currently, three-dimensional approaches are commonly used for joint angular kinematic investigations. However, recommendations by the International Society of Biomechanics are rarely considered.